Opportunities and Challenges in Immersive Entertainment - Lages, Wallace S. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19755, 2021)
The next major shift in digital entertainment will be the wide adoption of mixed reality platforms. Although owners of mixed reality devices are still a minority today, immersive systems are quickly getting better and cheaper. We identity eight research topics on immersive entertainment and discuss possible research directions that can lead to advances in the field